Fungsi Ruang Terbuka Hijau (RTH) di Kecamatan Biringkanaya Kota Makassar - Busrah, Nurul Latifah; Robert, Jan; Lululangi, Mithen (Pascasarjana Universitas Negeri Makassar, 2018)
This research is a quantitative descriptive study, which aims to determine the function of green open space in the Biringkanaya District of Makassar City. The research object is 3 RTH in Biringkanaya District. Data collection uses documentation techniques, interviews, observation, and surveys. The descriptive analysis showed that the average function of RTH in Taman Ayam Daya is 50%, which means the category is, Untia Mangrove Forest and Baddoka Golf Course is 77.78% which means good category. So the results of this study show that the Untia Mangrove Forest and Baddoka Golf Course have the highest percentage which means fulfilling functions among other green open spaces.